Morpho-physiological traits and stress indices reveal divergence in early-stage salt stress response in elite soybean germplasm - Muhammad Arif; Haris Khurshid; Malik Ashiq Rabbani; Muhammad Jahanzaib; Sahir Hameed Khattak; Ihsan Ullah; Mohammad Abul Farah; Rattandeep Singh; Luhua Li (Journal of King Saud University: Science)
This study assessed the salt stress response of seventy soybean genotypes by exposing seedlings to sodium chloride (NaCl) concentrations of 0, 75, 100, and 125 mM. Salinity stress significantly reduced root length, shoot length, fresh and dry root/shoot weight, and root/shoot ratio. A total of 62 genotypes germinated at 125 mM, showing significant phenotypic variation in traits such as root length, shoot length, fresh shoot weight, and dry shoot weight. Pearson’s correlation analysis revealed a strong positive correlation between most morpho-physiological traits, suggesting their interdependence. Eight salinity tolerance indices i.e., Fresh Weight Stress Tolerance Index (FWSI), Dry Weight Stress Tolerance Index (DWSI), Root Length Salinity Index (RLSI), Shoot Length Salinity Index (SLSI), Salinity Tolerance Index (STI), Salinity Susceptibility Index (SSI), Tolerance Index (TI), and Percent Reduction (PR) were calculated to assess genotypes response. Na+ concentration and antioxidant activities significantly increased under salt stress compared to the control. The activities of antioxidant enzymes, as well as the levels of reactive oxygen species (ROS) such as H2O2 and O2−, were markedly higher under salt stress compared to the control. Hierarchical cluster analysis grouped genotypes into six clusters, with clusters V and VI comprising genotypes exhibiting higher salt tolerance based on high FWSI, DWSI, and STI values, and low PR, SSI, and TI values. Eight salinity tolerance indices, including Fresh Weight Stress Tolerance Index (FWSI), Dry Weight Stress Tolerance Index (DWSI), Root Length Salinity Index (RLSI), and Salinity Tolerance Index (STI), were used to evaluate the genotypes’ responses. The study revealed that the average FWSI value for all genotypes under treatments was 54.20 ± 12.93. The highest FWSI was recorded for the genotype Black (92.52), followed by NIBGE-224 (84.70) and NIBGE-183 (81.05). In contrast, Malakand-96 had the lowest FWSI (28.49), followed by SPS-10 (32.74) and SPS-08 (34.55). PGRA-91 had the highest STI (0.83), followed by SPS-9 (0.75) and NIBGE-115 (0.72), while NIBGE-335, SPS-24, and Malakand-96 had the lowest STI values. Positive correlations were observed between root length and shoot length (0.69**), shoot length and fresh shoot weight (0.63**), and other related traits. Overall, this study identified promising soybean genotypes with varying degrees of salt tolerance. These findings can be utilized in breeding programs to develop salt-tolerant soybean varieties for salinity-affected agricultural lands.